ALGORITHM FOR FINDING DOMINATION RESOLVING NUMBER OF A GRAPH - Iqbal M. Batiha; Nidal Anakira; Basma Mohamed (Journal of Mechanics of Continua and Mathematical Sciences)
A minimum resolving set is a resolving set with the lowest cardinality and its cardinality is a dimension of connected graph , represented by . A dominating set is a set of vertices such that each of is either in or has at least one neighbor in . The dominance number of is the lowest cardinality of such a set. The lowest cardinality of the dominant resolving set is called a dominant metric dimension of , represented by . This paper presents an algorithm for finding the domination resolving number of a graph.